Metode Hermeneutika dan Permasalahannya Dalam Penafsiran Al-Quran - Taufik Mukmin (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2019)
Hermeneutics is a method or philosophical theory to interpret symbols related to the text in order to know the meaning and meaning. it was first used in the study of the Koran in the 19th century AD by Islamic scholars, but many scholars questioned it. This is because it can doubt the authenticity and sanctity of the Koran. Besides that, hermeneutics has been used to interpret bible to find its truth value. The Qur'an serves every question and objection from its readers, who come from various cultural backgrounds and scientific disciplines. Because the scriptures cannot speak for themselves, they need understanding, reading, interpretation and repetition of reinterpretations that are generally carried out by experts in the same way. In addition, the distance between the birth of the text and the period of interpretation is very long. For this reason, a methodological